Rendimiento de las escalas ATA vs. ACR TI-RADS en la valoración de riesgo de nódulos tiroideos. - Rojas-Borda, Felipe; Gonzales, Edgar; Saavera, Gina; Patiño, Pamela (Revista Argentina de Radiología, 2025)
Introduction: The study will compare the diagnostic performance of two risk scales to assess the outcome of thyroid cancer diagnosis. Objective: To compare the performance of the ATA and ACR TI-RADS classification systems in patients with thyroid nodules evaluated by ultrasound at Hospital Central Militar from January 2018 to January 2022. Method: Ambispective study to validate diagnostic tests in patients assessed for thyroid nodule biopsies by fine needle aspiration with definitive pathology results reported by the Bethesda system. Thyroid nodules were classified using the ATA (2015) and ACR TI-RADS (2017) scales. A descriptive analysis was performed for qualitative variables. For quantitative variables, measures of central tendency were obtained. A logistic regression was performed with the outcomes to calculate the sensitivity and specificity of the scales. Results: Thyroid nodules with the presence of microcalcifications, taller than wide and irregular margins were statistically significant associated with malignant thyroid nodules (p < 0.005). Results calculated for ACR TI-RADS: sensitivity 95.65%, specificity 26.32%, positive predictive value (PPV) 25.88%, negative predictive value (NPV) 95.74%. For ATA risk scale: sensitivity 97.83%, specificity 25.73%, PPV 26.16%, NPV 97.78%. Conclusion: The ACT TI-RADS and ATA scales have high sensitivity and high NPV as approach methods in the study of TN for risk stratification.